Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acsami.0c17180
|View full text |Cite
|
Sign up to set email alerts
|

Novel Homogeneous Anion Exchange Membranes for Reproducible and Sensitive Nucleic Acid Detection via Current–Voltage Characteristic Measurement

Abstract: One-pot synthesis of novel hydrogel-based anion exchange membranes (AEMs), with only a single-phase monomer mixture, was used to eliminate surface heterogeneity and generate reproducible electroconvective microvortices in the over-limiting region of the current−voltage characteristic (CVC) curves. Diallyldimethylammonium chloride (DDA) was used as the main component to provide the cation charge groups, and 2hydroxyethyl methacrylate (HEMA) and ethylene glycol dimethyl acrylate (EGDMA) were used as the auxiliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…These results allow one to quantitatively understand the fluid state and velocity statistics in the ECF and provide optimization guidance for the performance design of electromembrane microfluidic systems, such as desalination (Chuang et al 2020), mixing (Guan, Yang & Wu 2021), preconcentration (Qiu et al 2019), charge injection (Guan & Novosselov 2019) and electrodeposition (Chen et al 2016;Zheng et al 2020). In addition, our scaling analysis is performed on the case with the fixed dimensional Debye length, which is a limitation of the hypothetical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…These results allow one to quantitatively understand the fluid state and velocity statistics in the ECF and provide optimization guidance for the performance design of electromembrane microfluidic systems, such as desalination (Chuang et al 2020), mixing (Guan, Yang & Wu 2021), preconcentration (Qiu et al 2019), charge injection (Guan & Novosselov 2019) and electrodeposition (Chen et al 2016;Zheng et al 2020). In addition, our scaling analysis is performed on the case with the fixed dimensional Debye length, which is a limitation of the hypothetical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…To normalize with respect to variations in the sensor size and surface roughness, the voltage shift of the AEM sensor is calculated based on the over-limiting voltage at a current equal to twice the limiting current. 40,46 The limiting current (I lim ) is measured at the overlap of the slope of the ohmic and limiting regions, shown in Fig. 2A.…”
Section: Fabrication and Operation Of Integrated Dissociation And Sen...mentioning
confidence: 99%
“…However, all of these mechanisms have been studied in a fluid domain plus a perm-selective membrane without considering the possibility of network effects through multiple connected micropores or microchannels in the fluid domain. While Chuang et al and Sensale et al have reported vortices on the surface of the membrane, their system has no nonuniform structure in fluid domain. On the other hand, Yossifon et al presented nanoscale asymmetry in which the narrow and wide nanochannels interact with each other in nanoslots, showing nanochannel network effects, not microchannel network effects.…”
mentioning
confidence: 93%